Maternal secretin ameliorates obesity by promoting white adipose tissue browning in offspring. (2nd June 2022) - Xue, Lamei; Sun, Juan; Liu, Jinxin; Hu, Chaoping; Wu, Dandan; Nie, Chenzhipeng; Zhang, Kuiliang; Wang, Yu; Zhao, Lei; Li, Xihua; Lu, Yan; Zhang, Li; et al.
Abstract: Our knowledge of the coordination of intergenerational inheritance and offspring metabolic reprogramming by gastrointestinal endocrine factors is largely unknown. Here, we showed that secretin (SCT), a brain‐gut peptide, is downregulated by overnutrition in pregnant mice and women. More importantly, genetic loss of SCT in the maternal gut results in undesirable phenotypes developed in offspring including enhanced high‐fat diet (HFD)‐induced obesity and attenuated browning of inguinal white adipose tissue (iWAT). Mechanistically, loss of maternal SCT represses iWAT browning in offspring by a global change in genome methylation pattern through upregulation of DNMT1. SCT functions to facilitate ubiquitination and degradation of DNMT1 by activating AMPKα, which contributes to the observed alteration of DNMT1 in progeny. Lastly, we showed that SCT treatment during pregnancy can reduce the development of obesity and improve glucose tolerance and insulin resistance in offspring of HFD‐fed females, suggesting that SCT may serve as a novel biomarker or a strategy for preventing metabolic diseases. Synopsis: Maternal secretin promotes white adipose tissue browning in the offspring by inducing a global change in genome methylation pattern through the DNA methyltransferase DNMT1. Genetic loss of secretin in the maternal gut results in disrupted glucose and lipid homeostasis in the offspring. Maternal secretin promotes white adipose tissue browning in the offspring. Depletion of maternal SCT leads to an AMPKAα dependent increase in DNMT1 protein levels in the white adipose tissue of the offspring. Maternal secretin reprograms white adipose tissue methylation of the offspring. Abstract : Maternal secretin promotes white adipose tissue browning in the offspring by inducing a global change in genome methylation pattern through the DNA methyltransferase DNMT1.